1204Modelling impact of targeted hepatitis B treatment for culturally and linguistically diverse populations in Australia. (2nd September 2021) - Taye, Belaynew; Valery, Patricia; Clark, Paul
Abstract: Background: Antiviral treatment gap in culturally and linguistically diverse (CALD) populations may be a barrier progress in national elimination. Using modelling, we estimated and predicted the impact of antiviral treatment and migration on HBV burden, and HBV-related mortality in CALD populations in Australia. Methods: We developed a dynamic, deterministic mathematical model using three antiviral treatment scale-up scenarios - the baseline treatment, intermediate treatment scale-up (80% of eligible by 2030), and optimistic scale-up (20% of all HBV by 2022) to predict the incidence of HBV infection, liver cirrhosis, hepatocellular carcinoma, and HBV-related mortality in four groups of people according to their country of birth. Results: The number of chronic HBV cases will remain similar, and HBV-related morbidity and mortality will increase if the baseline approach is followed to 2030. Implementing an optimistic treatment scale-up could reduce the number of new cases of liver cirrhosis (30% in European-born, and 40% in Asia-Pacific-born) by 2030. Following the optimistic scale-up approach, the incidence of HCC decreased by 30% and a 15%-25% reduction in HCC-related mortality could be achieved in the four population subgroups by 2030. Conclusions: Following the current antiviral treatment coverage, HBV elimination targets in migrants may not be achieved. A rapid treatment scale-up approach reduces HBV incidence, liver cirrhosis and HCC. Key messages: Targeted antiviral treatment for migrants with HBV using rapid scale-up reduces HBV-related disease and mortality and contributes to achievement of national elimination targets.